The Structure of the Molecular Envelope of the Ring Nebula (NGC 6720) - Joel H. Kastner; David J. Wilner; Diana Ryder; Paula Moraga Baez; Orsola De Marco; Raghvendra Sahai; Alwyn Wootten; Albert Zijlstra (The Astrophysical Journal, 2025)
We present the first interferometric imaging of molecular line emission from the Ring Nebula, NGC 6720, in the form of Submillimeter Array (SMA) observations of CO J  = 2 → 1 emission. The SMA ^12 CO(2–1) mapping data, with ∼3″ spatial resolution and 2 km s ^−1 velocity resolution, provide an unprecedentedly detailed, 3D view of the Ring’s clumpy molecular envelope. The emission morphology displayed in the velocity-integrated SMA ^12 CO(2–1) image closely resembles the morphologies of near-IR H _2 and polycyclic aromatic hydrocarbon emission as revealed in recent JWST/NIRCam imaging of NGC 6720. The SMA ^12 CO(2–1) data demonstrate that the molecular gas is found within a geometrically thin layer that immediately surrounds the ionized gas imaged by Hubble Space Telescope and JWST. A simple, geometric model of the ^12 CO(2–1) emission data shows that the intrinsic structure of NGC 6720’s molecular envelope closely resembles a truncated, triaxial ellipsoid that is viewed close to pole-on, and that the dynamical age of the molecular envelope is ∼6000 yr. The SMA ^12 CO(2–1) mapping data furthermore reveal that some of the faint, filamentary features seen projected in the Ring’s interior in JWST imaging are in fact fast-moving polar knots or bullets with radial velocities of ±45–50 km s ^−1 relative to the systemic velocity, and that the hot progenitor star remnant is positioned at the precise geometric center of the clumpy, ellipsoidal molecular shell. We assert that the Ring’s molecular envelope represents the “fossil” remnant of a relatively sudden mass ejection ∼6000 yr ago that terminated the progenitor star’s asymptotic giant branch (AGB) evolution, and that this ellipsoidal envelope of AGB ejecta was then punctured by fast, collimated polar outflows or jets resulting from interactions between the progenitor and one or more companion stars. Such an evolutionary scenario may describe most if not all molecule-rich, “Ring-like” planetary nebulae.